Study of salivary IgA concentrations, salivary flow rate in patients with β -thalassemia major in Missan Governorate - Jamal M Diwan; Zaheda J Mohammad (College of Dentistry/ University of Baghdad, 2015)
Background: Beta-thalassemia major is the most common monogenic known disorder in the Middle East, characterized by anomalies in the synthesis of the beta chains of hemoglobin resulting in variable phenotypes ranging from severe anemia to clinically asymptomatic Individuals. This study aimed to evaluate salivary flow rate and salivary IgA in β-thalassemia major patients. Since many oral and systemic conditions manifest themselves as changes in the flow and composition of saliva the dental practitioner is advised to remain up-to-date with this issue. Materials and methods: The study samples consist of (60) subjects, patients group composed of (30) patients with β -thalassemia major, age rang (5-23) years and (30) healthy locking subject of both sexes as control group, with age range from (5-25) years. Results: Most patients were in the first and second decade of life (90%) this indicate a reduced life expectancy in those patients, laboratory investigations for salivary IgA concentrations revealed a significant increase in means of this marker in compare with control group and this difference is statistically significant, (p= 0.05) at P value ≤ 0.05.Regarding the salivary flow rate there was a statistically significant decrease in mean of salivary flow rate in patients group as compared with control group (P= 0.013). Conclusions: Beta-thalassemia major affects salivary flow rate and SIgA concentration.